Edge‐State‐Enhanced Ultrahigh Photoresponsivity of Graphene Nanosheet‐Embedded Carbon Film/Silicon Heterojunction. Issue 11 (26th April 2019) - Zhang, Xi; Lin, Zezhou; Peng, Da; Ye, Lei; Zang, Jianfeng; Diao, Dongfeng
Abstract: Lacking of electron trapping centers hinders the development of plane graphene for sensitive photodetection. An ultrasensitive graphene nanosheet‐embedded carbon (GNEC) film/silicon photodetector is proposed by introducing high‐density edges of standing structured graphene nanosheets (GNs). The GNEC film is prepared to contain a large amount of vertically grown GNs. The high‐density edges are able to trap itinerate electrons to tune the Fermi level of GNs in the growing process and to capture the photoexcited electrons to reduce the electron–hole recombination rate in the photovoltaic process. An ultrahigh responsivity of 61.52 A W −1 of GNEC film/Si photodetector is achieved, ≈20 times of graphene/Si photovoltaic detectors. A high specific detectivity of 3.05 × 10 14 Jones (approximately two orders improved) is obtained at bias‐free mode. This work sheds light on the edge engineering of 2D materials in the third dimension in order for enhancing photoelectronic performance. Abstract : Graphene edge states have superior properties for photo‐electron trapping. In this work, a van de Waals heterojuction is reported with an ultrahigh responsivity of 61.52 A W −1 and a high specific detectivity of 3.04 × 10 14 Jones. Edge state modulates the Fermi‐level and reduces the recombination rate of photo‐excited electron‐hole pairs.